Scientific and methodological basis for the creation of national regulatory framework for oil and fat industry - Петік, Павло Федорович; Федякіна, Зоя Павлівна; Григорова, Любов Іванівна; Тимченко, Валентина Кузьмівна; Левчук, Ірина Володимирівна (Technology audit and production reserves, 2015)
The results of the system scientific and methodical research on the national regulatory framework of oil and fat industry are first presented in the article. Based on the analysis of scientific literature and a series of national standards DSTU, DSTU ISO, DSTU Codex Stan, DSTU-P, ISO/TS, DSTU CAC/RCP (total 122 titles), created in the sectoral Ukrainian Scientific Research Institute of oils and fats, its classification is developed and the level of harmonization with European and international standards is defined According to the proposed classification of national standards can be divided into groups: terms and definitions; general specifications; methods of sampling, acceptance rules, methods for determination of organoleptic, physical-chemical, structural and safety performance; standards-orders; system of Standards of Ukrainian Companies of technological documentation. The features of the development of individual standards, such the use of the author's procedures of determining benzopyrene, waxes, mineral oil contaminants in vegetable oils, glucosinolates, and so on are marked. The level of harmonization of national standards with European and international standards, which is 0,27 and it is below the recommended level by program of integration into the European Union (0,8). The conclusions about the need are given for further review and the creation of new national standards for the oil and fat industry, improve their level of harmonization and the use of research results in the educational process of higher educational institutions on a specialty "Technology of fats and fat substitutes."